2016
DOI: 10.3354/meps11760
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lionfish increase activity and foraging movements at greater local densities

Abstract: Density-dependent changes in predator foraging behavior due to intraspecific competition for food can have important implications for population dynamics of both the predator and its prey. The Indo-Pacific red lionfish Pterois volitans is an invasive predatory reef fish that has reached high population densities and can cause large reductions in small native fishes. To determine whether lionfish behavior or movement varies with local lionfish and/or prey densities, I conducted observations of lionfish on 16 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 100 publications
1
21
0
Order By: Relevance
“…Counterintuitively, our results indicated that lionfish density on the adjacent artificial reef was not a significant predictor of lionfish recruitment nor catch. We had expected lionfish movement from reefs to traps would be driven by overcrowding given high lionfish densities have been related to local prey depletion [12,14,58], cannibalism [59,60], and lower body condition [53], and greater movement on coral reefs [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Counterintuitively, our results indicated that lionfish density on the adjacent artificial reef was not a significant predictor of lionfish recruitment nor catch. We had expected lionfish movement from reefs to traps would be driven by overcrowding given high lionfish densities have been related to local prey depletion [12,14,58], cannibalism [59,60], and lower body condition [53], and greater movement on coral reefs [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than many fisheries where removal efficiency is <10% [6365], but considerably lower than the >85% removal efficiency for spearfishing lionfish on nGOM artificial reefs [46]. Given spearfishing can reduce lionfish densities in areas frequented by divers [6668] and spearfishing fisheries have caused severe depletion of other reef fishes [6971], we expect spearfishing to remain the most efficient and cost-effective method for removing lionfish biomass at depths <40 m. Removal efficiencies and uncaptured lionfish will need to be considered when evaluating the potential community benefits offered by lionfish trapping as lionfish removals do not necessarily translate into ecological benefits [14,72,73] given lionfish predation [62,74], growth [53,75], and colonization [14,73,76] rates are controlled via density-dependent feedbacks. Ecosystem models may be appropriate for examining the potential community effects of a deepwater lionfish fishery [15,77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamate receptors have been shown to be under selection in other teleost fish species, including the European eel and small yellow croaker (Pujolar et al 2014b;Liu et al 2016). There is some evidence that behavioral movement patterns are changing as the lionfish invasion progresses (Benkwitt 2016), which could be related to changes in the pathways …”
Section: Outlier Analyses Identify Loci Primarily Without Blast Idsmentioning
confidence: 99%
“…sunrise, noon and sunset) to test the hypothesis of a crepuscular pattern in hunting activity (i.e. sunrise and sunset) as this has been shown in the Atlantic invasion (Cure et al 2012, Benkwitt 2016) and invoked as one of the behavioural traits facilitating their invasive success (i.e. increased hunting success and broader array of preys available) (Hobson 1973, Potts 1990, Green et al 2011).…”
Section: Introductionmentioning
confidence: 99%